The Use of Ulead Studio Program Products (UVIOPro) to Improve the Students’ Writing Skill - Junaid Junaid; Firman Firman (Acitya: Journal of Teaching and Education, 2023)
The study aims to find out whether or not the use of UVIOPro is effective to improve the students’ writing skill, particularly in terms of content, organization, and mechanics. This study applied a Quasi-Experimental design. The sample of this study was the second semester students of English Education department at Faculty of Teacher Training and Education at University of Muhammadiyah Makassar in academic year 2014/2015. Therefore, the sample was determined with a cluster random sampling by applying a lottery technique. Hence, it consisted of 60 students divided in two groups. The data were collected through writing test, which consisted of pretest and posttest. The data were analyzed by using descriptive and inferential statistics through SPSS version 20. The findings show that the students’ writing skill, particularly in terms of content, organization, and mechanics improved after giving the treatments. The results of t-test analysis for the students’ score improvement in terms of content and organization in experimental and control groups reveals that Sig. (2-tailed) is less than (α) = 0.05. Based on the findings, it can be concluded that the use of UVIOPro in teaching writing was effective to improve the students’ writing skill in terms of content, organization, and mechanics.